THE PROBLEM OF ACCESSIBILITY OF PSYCHOTEMPORAL MARKETING RESEARCH IN SMALL BUSINESS (INNOVATIVE ECONOMY, 2025)
Mykhailov A.R.  THE PROBLEM OF ACCESSIBILITY OF PSYCHOTEMPORAL MARKETING RESEARCH IN SMALL BUSINESSPurpose. The aim of the article is scientific substantiation and finding practical solutions for improving the accessibility of psychotemporal marketing research in small businesses in Ukraine, as well as to identifying effective tools for their application in the digital economy.Methodology of research. The following methods were used in the work, namely, methods of analysis and synthesis of modern scientific sources, comparative analysis of marketing research tools, expert assessment methods, as well as empirical approaches – online surveys, digital analytics analysis, and modelling using the SPIN interviewing scheme. The use of applied methods made it possible to obtain practical data on the possibilities of implementing psychotemporal approaches in small enterprises.Findings. It has been proven that psychotemporal marketing, based on taking into account the psychological and temporal characteristics of consumer behaviour, contributes to improving the effectiveness of small business communications. The main barriers to its implementation have been identified: the high cost of classical neuromarketing research, the lack of specialized knowledge, and the limited resources of entrepreneurs. At the same time, it has been established that there are a number of low-budget tools (digital analytics, A/B testing, UX analytics, online surveys, cooperation with universities) that can replace or imitate full-fledged laboratory methods. Practical results of testing on the example of the small enterprise Step-Psy showed an improvement in customer retention rates, an increase in session duration, and a decrease in the bounce rate.Originality. The article systematizes modern psychotemporal tools available to small businesses for the first time and demonstrates their integration into the digital environment of entrepreneurship. A concept of democratization of marketing research is proposed, which involves the gradual introduction of simplified but effective methods of neuromarketing and behavioural economics for SMEs.Practical value. The results of the study can be used by small business entrepreneurs to optimize marketing strategies, increase customer focus, and build sustainable competitive advantages. They are also of interest to educational and scientific institutions that train specialists in the field of marketing, as well as to government programs for the digital transformation of entrepreneurship.Key words: psychotemporal marketing, small business, digital tools, neuromarketing, behavioural analysis, customer focus.
Keywords: psychotemporal marketing; small business; digital tools; neuromarketing; behavioural analysis; customer focus